The bronze depot of Miljana - Anton, Smodić (Arheološki vestnik, 1956)
A depot of bronze articles was discovered by chance at M iljana in 1895. Among the finds w ere hammers, fragm ents of swords and spears, fragm ents of sickles and axes as w ell as pieces of bronze in the shape of plates or cakes. Typo[1]logicallv these objects belong to the Reinecke H allstatt A period an d partly to the H allstatt B period.